Pembinaan Kapasitas Manajemen “UMKM Go Digital” Di Kabupaten Bogor - Fadlillah, Alnisa Min; Fadila, Ardhiani; Husniati, Renny (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2021)
This company aims to help Indigenous UMKM in Bogor Regencyto increase their business management capacity by Going Digital to adjustcurrent technological developments. The service team conducts coaching(training and mentoring) to UMKM actors digitally. The materials weprovide are materials related to marketing management (productrebranding, digital marketing), Blue Ocean Strategy, Canvas Strategy, andfinancial management (financial techonology). Activities in a whole mannerincrease the knowledge and skills of UMKM HUMAN RESOURCES inrunning business in a sustainable manner.